Two-dimensional electrophoretic comparison of metastatic and non-metastatic human breast tumors using in vitro cultured epithelial cells derived from the cancer tissues - Vydra, Jan; Selicharová, Irena; Smutná, Kateřina; Šanda, Miloslav; Matoušková, Eva; Buršíková, Eva; Prchalová, Markéta; Velenská, Zuzana; Coufal, David; Jiráček, Jiří (BMC cancer, 2008)
BACKGROUND: Breast carcinomas represent a heterogeneous group of tumors diverse in behavior, outcome, and response to therapy. Identification of proteins resembling the tumor biology can improve the diagnosis, prediction, treatment selection, and targeting of therapy. Since the beginning of the post-genomic era, the focus of molecular biology gradually moved from genomes to proteins and proteomes and to their functionality. Proteomics can potentially capture dynamic changes in protein expression integrating both genetic and epigenetic influences. METHODS: We prepared primary cultures of epithelial cells from 23 breast cancer tissue samples and performed comparative proteomic analysis. Seven patients developed distant metastases within three-year follow-up. These samples were included into a metastase-positive group, the others formed a metastase-negative group. Two-dimensional electrophoretical (2-DE) gels in pH range 4-7 were prepared. Spot densities in 2-DE protein maps were subjected to statistical analyses (R/maanova package) and data-mining analysis (GUHA). For identification of proteins in selected spots, liquid chromatography-tandem mass spectrometry (LC-MS/MS) was employed. RESULTS: Three protein spots were significantly altered between the metastatic and non-metastatic groups. The correlations were proven at the 0.05 significance level. Nucleophosmin was increased in the group with metastases. The levels of 2,3-trans-enoyl-CoA isomerase and glutathione peroxidase 1 were decreased. CONCLUSION: We have performed an extensive proteomic study of mammary epithelial cells from breast cancer patients. We have found differentially expressed proteins between the samples from metastase-positive and metastase-negative patient groups.
Keywords: financování organizované; dospělí; metastázy nádorů; 2D gelová elektroforéza; nádory prsu; Female; Adult; ženské pohlaví; peptidové mapování; lidé; proteomika; Epithelial Cells; Breast Neoplasms; Aged, 80 and over; nádorové buňky kultivované; Peptide Mapping; Middle Aged; Financing, Organized; Proteomics; Tumor Cells, Cultured; Aged; Electrophoresis, Gel, Two-Dimensional; nádorové proteiny; Neoplasm Proteins; lidé středního věku; senioři nad 80 let; senioři; Neoplasm Metastasis; epitelové buňky; Humans